FRI0607-HPR FREQUENCY AND PATIENTS BELIEFS ON VACCINATION IN RHEUMATIC DISEASES. (2nd June 2020) - Viola, M.; Benitez, A.; Garbarino, C.; Rodriguez, G.; Benavidez, F.; Peon, C.; Blanco, E. S.; Molina, H.; Gómez, G.; Redondo, G.; Delavega, M.; Mata, D.; et al.
Abstract : Background: Infectious diseases are increased in patients with rheumatic disorders; vaccination improves morbidity and mortality Objectives: The aim of this study was to describe the frequency of vaccination in patients with rheumatic disorders and to compare the results with those obtained in 2009 and 2013 in a similar population. We also identified factors leading to lack of vaccination and patients beliefs on vaccines. Methods: Multicentric cross sectional study in patients with autoinmune diseases from external rheumatology offices. Evaluation of vaccination status and patients´ knowledge about vaccines were studied. A comparative analysis was carried out with the series registered in 2009 and 2013 in a similar population. Results: 179 patients (158 female, 88.3% and 21 male, 11.7%) were evaluated. Median age was 52 years. Main pathologies were: Rheumatoid Arthritis 65.9% (n:118), Systemic Lupus Erythematosus 11.7% (n:21), Systemic Sclerosis 3.9% (7), Sjogren Syndrome n = 3.4% (n:6), other diseases 15% (n: 27). Median disease duration: 8.87 years. Ninety three percent of patients (n:167) were taking inmunomodulators and 36.8% (n: 66) were using oral corticosteroids (20mg/day or less); 26, 8% patients (n: 48) were receiving biological therapies. Vaccination frequency in the population was: Influenza 82% (147); 13-valent conjugate pneumococcal 69.3% (124), 23-valent pneumococcal 64.2% (115) and hepatitis B 62% (111). Comparative with 2009 and 2013 series there was an increase in the rate of vaccinated patients: influenza (82% vs. 39, 1% and 74, 2% respectively), antineumococcal (64% vs. 17% and 29%) and hepatitis B (62% vs. 6, 7% and 26, 7%). Reasons for non-vaccination were absence of medical indication (41% of patients for hepatitis B; 32% for 23-valent pneumococcal; 38% for 13-valent pneumococcal and 34% for influenza). 139 patients (77, 7%) knew the benefits of vaccines, 164 (91, 6%) thought vaccines are useful; 134 (74, 9%) reported that vaccines may decrease dying probability, 155 (86, 5%) thought that vaccines are effective to prevent diseases and 149 patients (83, 2%) believed that they prevent serious infections. 71 patients (39%) believed that vaccines can lead to serious consequences and 99 (55, 3%) that they are more likely to acquire infections than the rest of the population. Conclusion: Frequency of vaccination has increased since 2009 but there is still misinformation regarding vaccines risks and benefits. Promotion and information is essential to improve adherence. References: [1]2019 update of EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Furer V, et al. Ann Rheum Dis 2020;79:39–52 [2] Vaccines and Disease-Modifying Antirheumatic Drugs: Practical Implications for the Rheumatologist. Friedman MA et al. Rheum Dis Clin North Am. 2017 Feb; 43 (1):1-13. [3] Recommendations and barriers to vaccination in systemic lupus erythematosus. Garg M et al. Autoimmun Rev. 2018 Oct; 17 (10):990-1001. [4] Comparison of national clinical practice guidelines and recommendations on vaccination of adult patients with autoimmune rheumatic diseases. Papadopoulou D. et al. Rheumatol Int. 2014 Feb;34 (2):151-63. [5] Guías de recomendaciones de prevención de infecciones en pacientes que reciben modificadores de la respuesta biológica. Jordán R. Et al. Rev Arg Reumatol. 2014; 25 (2): 08-26. Disclosure of Interests: Malena Viola: None declared, Alejandro Benitez: None declared, Cecilia Garbarino: None declared, Gonzalo Rodriguez: None declared, Federico Benavidez: None declared, Claudia Peon: None declared, Eliana Soledad Blanco: None declared, Hernan Molina: None declared, Gimena Gómez: None declared, griselda redondo: None declared, Maria DeLaVega: None declared, Dario Mata: None declared, Augusto Riopedre: None declared, Osvaldo Messina Speakers bureau: Amgen; Americas Health Foundation; Pfizer